The Effects of Cooperative Learning Model Make A Match Type to the Students’ Knowledge and Attitudes Competence on Organization of Life System Material in SMPN 13 Padang - Yeny Nur Fasella; Heffi Alberida; Relsas Yogica (Bioeducation Journal, 2018)
The learning process at SMPN 13 Padang is teacher-centered, that effects students are less active. Teachers have not implemented innovative learning model, this makes students bored and lack of concentration during the learning process. When group discussions are held, students can not cooperate and communicate well. This resulted low competence knowledge and attitude of students, so it is necessary learning process that can improve the competence of knowledge and attitude of students by apply cooperative learning model type make a match. The purpose of this research to determine the positif effect of the model of cooperative learning type make a match to the competence of knowledge and attitude of students on the material organizational system of life in SMPN 13 Padang. This research is a experimental research with Randomized Control-Group Pretest-Posttest Design. The population of this research is students of class VII SMPN 13 Padang. Sampling by purposive sampling technique with VII.2 students as control class and VII.4 as experiment class. The research instruments are test for knowledge competence and observation sheet for attitude competence. The research hypothesis was tested by t-test. The result showed that eksperimental class and control class have different achievement of the knowledge competence with t calculate is 3,07 and t table is 1,669 and attiude competence with t calculate is 3,98 and t table is 1,669 with α 0,05. It showed that t calculate > t table, so it concluded that the implementation of cooperative learning model type make a match can improve the competence of knowledge and attitude of learners on the material organizational system of life in SMPN 13 Padang.